The Historical Study of the Grounds and Applicability of Iranian Literature’s Effect on Arabic Literature as well as Its Consequences in the First Islamic Centuries - Amir Hossein Hatami; Hassan Allahyari (تاریخ اسلام)
Of the consequences of Islam religion and the revelation of the Holy Quran in Arabic language, is the independence of this language from the restriction of ignorant Arab and it’s altering into the first and formal language in the world of Islam with a variety of political, scientific, cultural, social and economical domains. It is evident that the Arabic language due to its merely application in speech in a rather limited geographic location within the ignorance era could not be of this grand position in the world of Islam. Accordingly, throughout the confirmation of Islam religion, the initiate of grand conquests, as well as the development of caliphate and bureaucracy, the Muslims had to take advantage of the language, literature and culture of other nations in favor of enriching Arabic language and literature and due to various historical reasons and distinctive properties, Arabic language could achieve the first position and considerably affect on the holy language of Muslims. This article has endeavored to historically study the background and applicability of Iranian effects on Arabic language and some of its consequences during the first Islamic centuries